Understanding the Pattern Language of Residential Architecture Based on the Theories of “A Pattern Language” by Christopher Alexander - Naserabadi, Moloud Dashti; Yousefizadeh, Zeynab (Journal of History Culture and Art Research, 2017)
Pattern language is not a designing method and it has never been claimed that it could be a designing method. Pattern language has always been an attempt to integrate and unify patterns in the designing of a real project. Pattern language will only be useful after the completion of design work for analyses that are done on projects. But in fact, a set of interrelated patterns creates a framework by which it is possible to obtain any kind of design. Architectural plans that are consistent with a framework of Alexander’s patterns or foster and develop a framework of Alexander’s patterns will be felt more natural than other plans. In terms of objective, the present study is an applied research and it has been conducted by analytical-descriptive approach. In the present study, both quantitative and qualitative research techniques were applied for data collection. Also, data collection has been done by library research. Identification and analysis of vernacular housing, the effect of climate on vernacular architecture and using it in the new architecture are applied to achieve an appropriate model. Since the climate and culture are the most influential factors in the formation of vernacular housing body, so the factors originating from the climate and culture such as the orientation of buildings are identifying elements of vernacular architecture. Using the principles and criteria of these factors in contemporary and regional housing designs gives back the identity to housing architecture.